Advanced Digital Health Systems for Medical Records and Health Informatics Management - Bahri, Abdullah Othman Ali; Arwa Walan Alasmari; Mushabbab Ruddah T Albaqami; Aeshah Mohammad Ali Mathkur; Amal Zayed Muaysh Alazmy; Huthayfah Yahya Jabril Hakami; Yazeed Mohammed Alzaid; Badr Mohammed Ali Alsahli; Abdullah Ali A Aldhmaly; Majed Mufreh Bakhit Al-Otaibi; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Digital health integrates information and communication technologies into healthcare to improve disease management, enhance access, and promote patient-centered care. It encompasses telemedicine, wearable devices, mobile health applications, and health information systems, offering solutions to systemic inefficiencies and health disparities. Aim: This paper aims to explore the functions, categories, clinical significance, and implementation challenges of digital health technologies, while highlighting competencies required for entrepreneurship and interprofessional collaboration. Methods: A comprehensive review of current digital health frameworks, applications, and educational models was conducted. The analysis focused on technological categories, clinical applications, and barriers to adoption, including regulatory, validation, and security concerns. Results: Digital health improves patient engagement, facilitates remote monitoring, and supports predictive analytics for population health. It enhances workflow efficiency and care coordination through electronic health records and decision-support systems. However, challenges persist in clinical validation, regulatory clarity, scalability, and data security. Interprofessional collaboration and structured education are critical for successful integration. Conclusion: Digital health holds transformative potential for modern healthcare, enabling personalized, data-driven care and improving accessibility. Overcoming barriers related to validation, regulation, and privacy is essential for sustainable adoption. Education in digital health entrepreneurship and leadership will prepare professionals to innovate and implement these technologies effectively.